Ιδιωτική Σχολή Ξένων Γλωσσών και Ελληνικών Μαθημάτων. 1920-1950 Βιογραφία ενός σχολείου της Λεμεσού. (Foreign Languages & Greek courses Private School. 1920-1950. The Biography of a School in Limassol) - Papadima-Sophocleous, Salomi (My University, 2020)
N/A